Susceptibility-guided vs. empirical 10-day quadruple treatment for Helicobacter pylori-infected patients: A prospective clinical trial of first-line therapy - Li, Peiwei; Jin, Jing; Chen, Yan; Ma, Jianjuan; Du, Qin; Han, Yuehua (Frontiers in Microbiology, 2022)
Background: The increasing antimicrobial resistance of Helicobacter pylori (H.pylori) has resulted in a fall in cure rates. We aimed to assess the effectiveness of first-line susceptibility-guided therapy and furazolidone-based quadruple therapy for H pylori-infected patients. Methods: Subjects with H.pylori infection were randomly assigned to either 10-day susceptibility-guided treatment or empiric treatment in a 2:1 ratio. Susceptibility-guided therapy was based on susceptibility to clarithromycin, and patients with susceptible strains received clarithromycin 500 mg twice daily and otherwise minocycline 100mg twice a day was administered. Patients in the empiric therapy group was treated with furazolidone 100mg twice a day. During treatment, all patients were given esomeprazole 20 mg twice daily, colloidal bismuth pectin 200 mg twice daily, and amoxicillin 1 g twice daily. Results: A total of 248 patients were screened and 201 were finally included. Susceptibility-guided and empiric regimens were both successful with per-protocol eradication rates of 90.5% (57/63) vs. 88.5% (108/122) (p=0.685) and intent-to-treat eradication rates of 85.1% (57/67) vs 80.6% (108/134) (p=0.435). No significant difference in eradication rates were observed among the furazolidone group, clarithromycin group and minocycline group. Conclusion: Both susceptibility-guided therapy and quadruple therapy containing furazolidone can achieve good eradication rates. For population with a high rate of resistance, quadruple therapy containing furazolidone and bismuth may be a more practical choice for fist-line treatment.